2022
DOI: 10.12998/wjcc.v10.i1.217
|View full text |Cite
|
Sign up to set email alerts
|

Superior mesenteric venous thrombosis: Endovascular management and outcomes

Abstract: BACKGROUND Superior mesenteric venous thrombosis (SMVT) is a rare but fatal condition that is typically treated initially with anticoagulation therapy, and if this fails, with endovascular interventions. However, due to its rarity, there are not many studies that have explored the effectiveness of anticoagulation and endovascular therapies in treating SMVT. AIM To evaluate patients diagnosed with SMVT who received endovascular therapy in addition to anticoagulation and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…Only two patients had complications requiring intervention. A technical success rate of 75–82% has been reported for EVTs [ 17 , 24 , 25 , 32 ]; therefore, we achieved a high recanalization rate. In terms of complications, Hollingshead et al reported that 60% of their patients experienced major complications, and one patient died of gastrointestinal bleeding and sepsis [ 24 ].…”
Section: Discussionmentioning
confidence: 59%
See 3 more Smart Citations
“…Only two patients had complications requiring intervention. A technical success rate of 75–82% has been reported for EVTs [ 17 , 24 , 25 , 32 ]; therefore, we achieved a high recanalization rate. In terms of complications, Hollingshead et al reported that 60% of their patients experienced major complications, and one patient died of gastrointestinal bleeding and sepsis [ 24 ].…”
Section: Discussionmentioning
confidence: 59%
“…In terms of complications, Hollingshead et al reported that 60% of their patients experienced major complications, and one patient died of gastrointestinal bleeding and sepsis [ 24 ]. Alnahhal et al reported a complication rate of 8.3% [ 17 ]. Contrastingly, although the complication rate in our study was high, no procedure-related death occurred, and all complications could be treated with either transfusion or transarterial embolization.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In recent years, the application of interventional therapy for this type of vascular disease has become increasingly extensive, which can significantly shorten hospitalization time and trauma, accelerate postoperative recovery, and restore the blood vessels of the infarcted intestinal tract as soon as possible ( 2 ). The surgical methods of interventional therapy include fragmentation, crushing, and suction, especially percutaneous mechanical thrombectomy in the treatment of thrombus, which can reduce the dose of thrombolytic agents and speed up the postoperative recovery of patients ( 12 , 13 ). In 46 patients with portal vein PV-SMV thrombosis, Liu et al found that the efficacy of direct injection of a thrombolytic agent into the catheter significantly improved the thrombolytic effect and reduced related bleeding complications ( 14 ).…”
Section: Discussionmentioning
confidence: 99%